AMELIORATIVE EFFECT OF Phoenix dactylifera EXTRACT ON MORPHINE-INDUCED DAMAGE OF SPERM QUALITY AND TESTICULAR HISTOLOGY IN RATS - Noor Hashida Hashim; Noor Eliza Hashim; Faridah Sonsudin; Noor Hazwani Hamidy; Amirah Baharin (Journal of Animal and Plant Sciences, 2024)
Forty Sprague-dawley male rats were divided into 4 groups; Control, rats were forced feed with distilled water, 35 days; Morphine, rats were intramuscularly injected with morphine (20 mg/kg), 7 days; P. dactylifera (date), rats were forced feed with date aqueous extract, 28 days, and Morphine-P. dactylifera, rats were injected with morphine (20 mg/kg), the first 7 days and forced feed with date aqueous extract, another 28 days. The testis and epididymis were harvested for histological and sperm parameter analysis. The Morphine- P. dactylifera group showed significantly higher sperm count (109.30 ± 5.01 x 106 sperm/ml) and motility (72.80 ± 4.48 x 106 sperm/ml) than the morphine group (P < 0.05). Significantly higher normal and lower abnormal sperm were observed in the Morphine- P. dactylifera group in comparison to the Morphine group. Higher in life sperm (90.50 ± 0.00 %) and lower in dead sperm (9.50 ± 0.00 %) were also observed in the Morphine- P. dactylifera group than the Morphine group. Testicular cells were found to be significantly higher in Morphine- P. dactylifera group as compared to the Morphine group. These research findings have provided additional information on the beneficial effect of P. dactylifera to ameliorate the damages caused by morphine on sperm parameters and testicular histoarchitecture. Thus, this study may suggest the potential use of P. dactylifera as a supplement to improve male reproductive functions.
Keywords: Phoenix dactylifera; morphine; sperm; testis; rats